Stressing out the mitochondria: Mechanistic insights into NLRP3 inflammasome activation. Issue 2 (27th December 2018) - Yabal, Monica; Calleja, Dale J.; Simpson, Daniel S.; Lawlor, Kate E.
Abstract: Inflammasomes are multimeric protein complexes that induce the cleavage and release of bioactive IL‐1β and cause a lytic form of cell death, termed pyroptosis. Due to its diverse triggers, ranging from infectious pathogens and host danger molecules to environmental irritants, the NOD‐like receptor protein 3 (NLRP3) inflammasome remains the most widely studied inflammasome to date. Despite intense scrutiny, a universal mechanism for its activation remains elusive, although, recent research has focused on mitochondrial dysfunction or potassium (K + ) efflux as key events. In this review, we give a general overview of NLRP3 inflammasome activation and explore the recently emerging noncanonical and alternative pathways to NLRP3 activation. We highlight the role of the NLRP3 inflammasome in the pathogenesis of metabolic disease that is associated with mitochondrial and oxidative stress. Finally, we interrogate the mechanisms proposed to trigger NLRP3 inflammasome assembly and activation. A greater understanding of how NLRP3 inflammasome activation is triggered may reveal new therapeutic targets for the treatment of inflammatory disease. Abstract : Review of the ambiguities surrounding mitochondrial damage‐mediated activation of NLRP3, including new models for how cell death may activate NLRP3 to influence inflammation.